(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
The sweeping trend of communication technologies increasingly makes computers and computer-based operations an indispensable part of our everyday lives. Education as a institution deeply rooted within the context of the broader community can, therefore, hardly afford to do without the digital era. Assessment, as a subcategory of education, is expected to be under the influence of the same trend. The present study, focusing on the EFL situation in Iran compared two equal-sized advanced learners each containing 20) writing accuracy and length. One group employed the traditional paper-and-pencil PPT) mode while the other used computer-assisted language testing CALT). Results indicated a significantly more accurate writing for the CALT group, while a longer writing production for the PPT group. Implications of the study are discussed.